The development of Afghanistan's Integrated Package of Essential Health Services: Evidence, expertise and ethics in a priority setting process. (July 2022) - Lange, Isabelle L.; Feroz, Ferozuddin; Naeem, Ahmad Jan; Saeedzai, Sayed Ataullah; Arifi, Fatima; Singh, Neha; Blanchet, Karl
Abstract: Health systems in fragile states need to respond to shifting demographics, burden of disease and socio-economic circumstances in the revision of their health service packages. This entails making difficult decisions about what is and is not included therein, especially in resource-constrained settings offering or striving for universal health coverage. In this paper we turn the lens on the 2017–2021 development of Afghanistan's Integrated Package of Essential Health Services (IPEHS) to analyse the dynamics of the priority setting process and the role and value of evidence. Using participant observation of meetings and interviews with 25 expert participants, we conducted a qualitative study of the consultation process aimed at examining the characteristics of its technical, socio-cultural and organisational aspects, in particular data use and expert input, and how they influenced how evidence was discussed, taken up, and used (or not used) in the process. Our analysis proposes that the particular dynamics shaped by the context, information landscape and expert input shaped and operationalized knowledge sharing and its application in such a way to constitute a sort of "vernacular evidence". Our findings underline the importance of paying attention to the constellation of the priority setting processes in order to contribute to an ethical allocation of resources, particularly in contexts of resource scarcity and humanitarian need. Highlights: Describes the process of Afghanistan's latest health system revision. Examines the complex process of priority setting in a fragile state. Vernacular evidence is created through expert consultation where data gaps exist. Unpacking the constellation of expert input is critical in priority setting. Balanced process facilitation improves discussion around ethical resource allocation.